Impacts of obstetric violence in Brazil: a literature review (Research, Society and Development, 2023)
Obstetric violence (OV) is considered a global public health problem, and can be defined as any practice against women's sexual and reproductive health, and can also be considered an appropriation of the female body, characterized by dehumanized treatment, in which its main characterizations are: physical, psychological and sexual violence. OV is still little perceived and supported by the law, compared to other forms of violence against women, and discussions on the subject are relevant. Thus, the objective of this work is to discuss the effects of obstetric violence, seeking to give visibility, raise awareness and encourage the prevention of this violence that is part of the Brazilian reality. For this, the work was carried out through an exploratory descriptive bibliographical research, characterized by a review of references already analyzed and published. The following databases were used: Google Scholar, Scopus and Scielo, using the keywords: “obstetric violence”, “Brazil”, “childbirth”, “pregnancy”, “humanized childbirth”, “obstetric violation” and their combinations. Obstetric violence represents an impasse for the fulfillment of women's rights, as it is perceived as an increasingly common situation in their daily lives, whether in prenatal, delivery, postpartum or abortion situations. More robust, interdisciplinary and transnational research is needed to help policymakers, maternity care providers, women and families who access maternity services to better understand, define and address this phenomenon.